Design and test of flexible chassis automatic tracking steering system - Shujie, Song; Yining, Li; Jiwei, Qu; Wei, Zhou; Kangquan, Guo (International Journal of Agricultural and Biological Engineering, 2017)
In order to develop an innovative omnidirectional non-homonymic flexible chassis (FC), the four-wheel steering control method of FC was designed by a new concept called off-centered steering (OCS) and the automatic tracking steering system was analyzed. Novelty of this wheel concept lies in the non-conventional positioning of the steering axis and wheel axis. Additionally, the steering axis of steerable wheel was motorized with an on/off electrometrical brake to overcome a hyper-motorization issue inherent to the wheel’s geometrical properties and hold the steering position. Based on the off-centered steering characteristics of FC, the Wheatstone bridge was applied in the steering control system. The bridge resistances are used to track target steering angles and the actual steering angle, respectively. The output voltage of the bridge is exploited to adjust the wheel’s speed so that steering and automatic tracking could be achieved. Experiments at different speeds, loadings, and target steering angles were conducted. Results showed that the chassis can indeed be controlled independently and its steering range is from –90° to 90°, which indicated the automatic tracking steering system was effective. The electromagnetic lock (EL) can significantly improve the stability of the chassis and reduce the vibration. Loading has no significant effect on the accuracy of the steering angle and the time it takes to complete steering tasks. The time taken to complete a forward steering task showed a linear relationship with the required angles, but was independent of rotation speed; for backward steering, time was related to both target angles and rotation speed. The results presented in this research may provide a reference for the steering control strategies of the four-wheel individual drive and four-wheel (4WID/4WIS) vehicle in the future.Keywords: electric vehicles, flexible chassis, four-wheel steering, automatic tracking, control systemDOI: 10.25165/j.ijabe.20171005.2525Citation: Song S J, Li Y N, Qu J W, Zhou W, Guo K Q. Design and test of flexible chassis automatic tracking steering system. Int J Agric & Biol Eng, 2017; 10(5): 45–54.